Improvement of parents' oral health knowledge by a school-based oral health promotion for parents of preschool children: a prospective observational study - Zhiyi Shan; Chongshan Liao; Jiajing Lu; Cindy Po Wan Yeung; Kar Yan Li; Min Gu; Chun Hung Chu; Yanqi Yang (BMC, 2023)
Abstract Background Parents of preschool children have inadequate oral health knowledge in Hong Kong. Parents play a critical role in preschool children's dietary patterns and oral health behaviors. A school-based oral health promotion (OHP) for parents of preschoolers was developed and investigated. Objectives The objective of this study was to evaluate effects of the school-based OHP for parents of preschool children on parents' oral health knowledge and preschool children's early childhood caries (ECC). Materials and methods This was a quasi-experimental study. Parents of preschool children were divided into the intervention group (IG) and the control group (CG) according to their own selection. Parents in the IG participated in a structured school-based OHP workshop, while those in the CG did not attend the OHP workshop. Parents in both groups were invited to complete a questionnaire assessing their oral health knowledge before (T0), one month after (T1), and twelve months after (T2) the OHP workshop. Preschool children's caries was examined via dmft score at T0 and T2. Results Parents' oral health knowledge was negatively correlated with preschool children's dmft scores (R = -0.200, P < 0.001). Oral health knowledge was significantly improved in IG (P < 0.001) but not in CG (P = 0.392) at T1. Both groups experienced a significant improvement in oral health knowledge from T0 to T2 (P < 0.001). Parents' oral health knowledge in the IG was significantly higher compared to the CG at T1 (P < 0.001), but difference in the scores at T2 between the two groups showed no significant difference (P = 0.727). No significant difference was found in changes in children's dmft score from T0 to T2 between the IG and CG (p = 0.545). Conclusion Preschool children's high ECC is associated with the limited oral health knowledge of their parents. The school-based OHP workshop for parents increased parents' oral health knowledge within one month. This positive effect was maintained for twelve months and can be extended to a larger scale in the school setting.